1993
DOI: 10.1200/jco.1993.11.10.2036
|View full text |Cite
|
Sign up to set email alerts
|

Five-year administration of fenretinide: pharmacokinetics and effects on plasma retinol concentrations.

Abstract: 4HPR, at 200 mg/d for 5 years, resulted in constant drug plasma levels and constant retinol level reduction. After treatment interruption, 4HPR plasma concentrations decreased at the limit of detectability at 6 months and baseline retinol plasma concentrations were recovered after 1 month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
132
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(135 citation statements)
references
References 18 publications
2
132
1
Order By: Relevance
“…This compound is not an impurity in HPR because it was not found in the administered HPR solution and its concentrations increased with time. Neither RA nor MPR, a major HPR metabolite, which reaches in human plasma concentrations similar to those of the parent drug (Formelli et al, 1993), was detected in either cell line, thus indicating that such metabolic pathways do not occur in the cells.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This compound is not an impurity in HPR because it was not found in the administered HPR solution and its concentrations increased with time. Neither RA nor MPR, a major HPR metabolite, which reaches in human plasma concentrations similar to those of the parent drug (Formelli et al, 1993), was detected in either cell line, thus indicating that such metabolic pathways do not occur in the cells.…”
Section: Discussionmentioning
confidence: 85%
“…We have shown that when A2780 ovarian tumour cells, which are very sensitive to the growth inhibitory effect of HPR, were exposed continuously to the retinoid HPR, they became resistant. The growth of A2780 cells was 50% inhibited by 1 µM HPR, a pharmacologically achievable concentration (Formelli et al, 1993), whereas concentrations 10 times higher, probably associated with severe side effects, were required to obtain the same effects in A2780/HPR cells. The resistance to HPR was reversible, thus indicating that the presence of the drug is necessary to maintain the resistance phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were instructed to take 3 capsules of 4-HPR (100 mg/capsule) once daily with the largest meal of the day. To reduce the potential for ocular toxicity, patients were instructed not to take 4-HPR for 3 days following each monthly visit; this served as a 3-day drug holiday (18,19). Patients were allowed to continue medications for coexisting medical conditions and remained on NSAID and low-dose prednisone regimens.…”
Section: Methodsmentioning
confidence: 99%
“…4-HPR has potent preventive effects in rodent mammary tumour models (Crist et al, 1997;Moon and Constantinou, 1997). Interestingly, 4-HPR has been found to accumulate preferentially in breast tissue (Formelli et al, 1993). Based on its low toxicity profile, it is currently being tested in a large breast cancer prevention trial (Costa et al, 1994).…”
mentioning
confidence: 99%